2013
DOI: 10.15376/biores.8.3.4619-4632
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fiber Type and Coupling Treatment on Properties of High-Density Polyethylene/Natural Fiber Composites

Abstract: High-density polyethylene (HDPE) and natural fiber composites were prepared by melt compounding and injection molding. The influence of fiber type (i.e., pine, bagasse, rice straw, and rice husk) and the addition of coupling agents on the composite properties were investigated. The use of 30 wt% fiber enhanced the tensile and flexural properties of neat HDPE, but decreased the impact strength. The comprehensive mechanical properties of HDPE/natural fiber composites were significantly improved by the addition o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 33 publications
(33 reference statements)
1
18
0
1
Order By: Relevance
“…Further, the addition of SA and combination of SA and MAPP to the PP/VF composite has raised the strength to 46% and 50%, respectively. This clearly demonstrates that the strength largely depends on both the fiber dispersion as well as the fiber–matrix interaction …”
Section: Resultsmentioning
confidence: 83%
“…Further, the addition of SA and combination of SA and MAPP to the PP/VF composite has raised the strength to 46% and 50%, respectively. This clearly demonstrates that the strength largely depends on both the fiber dispersion as well as the fiber–matrix interaction …”
Section: Resultsmentioning
confidence: 83%
“…These results indicated that the percentages of unoxidized carbon atoms decreased and significant surface oxidation occurred. In addition, increases in these oxygen-containing functional groups and chemical bonds were observed after 2500-hour UV exposure, which was due to the formation of carbonyl by the fracture chain of the HDPE and the C═O groups in the lignin degraded by the photooxidation of the composites, 44,45 corresponding to the results of the abovementioned FTIR analysis. The C ox/unox ratio denotes the oxidation degree of the sample surface.…”
Section: Mechanism Analysismentioning
confidence: 77%
“…Polietilen graft maleik anhidrit (MAPE) lignoselülozik lif yüzeyindeki hidroksil grubu ile reaksiyona girmekte ve ester bağı oluşturmaktadır. Bu reaksiyonlar kompozitlerin fiziksel ve mekanik özelliklerinin iyileşmesini sağlamaktadır (Lu et al 2005, Liu et al 2013, Maiottti et al 2014. MCC liflerinin hidrofilik özelliğinden dolayı nonpolar ve hidrofobik özellikteki polimer matrisi arasındaki uyumsuzluğun bazı kimyasallar kullanılarak azaltılabildiği bazı araştırmacılar tarafından da belirlenmiştir (Qiu et al 2006, Sun et al 2014, Ifuku et al 2015, Zulkifli et al 2015.…”
Section: Introductionunclassified